Stop, Question, and Frisk in New York City: A Study of Public Opinions. (August 2017) - Evans, Douglas N.; Williams, Cynthia-Lee
New York City's Stop-and-Frisk program has been a contentious police practice for more than 40 years. There is extensive research that examines attitudes toward the police; however, empirical research has yet to analyze citizens' perceptions of stop-and-frisk. This study uses data from pedestrians to uncover their opinions of stop-and-frisk. Results demonstrate that several demographic characteristics predicted attitudes toward stop-and-frisk; minorities and younger citizens had less positive views, and unfavorable opinions were linked to living in New York City; having less education; being unemployed; having lower income; not married; no children; having been previously frisked by police; and vicarious experiences of others with stop-and-frisk. The results provide insights into demographic and experiential factors that influence attitudes toward stop-and-frisk. As perceived unfairness often undermines police authority, identifying factors that predict unfavorable attitudes toward police practices can aide in allocating resources to further efforts to improve police–community relations.